Comparison of Fasting Blood Glucose Levels Based on Light Exposure on Glucose Strips Using Point Of Care Testing (POCT) - Lia Mar’atiningsih; Ai Erlinawati; Desy Syswianti; Sabila Afsyaina Arrifa (PPNI UNIMMAN, 2023)
A blood sugar test is an examination procedure performed to determine blood sugar levels in the body. This study entitled